Association between ERCC2 Lys751Gln, Asp312Asn, and Arg156Arg polymorphisms and gynecological cancer susceptibility: a meta-analysis - Chen, Fen; Yu, Jiayang; Wang, Chun-Guang (Frontiers in Oncology, 2025)
BackgroundGynecological tumors are diseases that pose serious threats to women’s health. Cervical, endometrial, and ovarian cancers are the most common gynecologic tumors. Excision repair cross-complementation group 2 (ERCC2) plays a critical role in nucleotide excision repair. Polymorphisms in ERCC2 can influence DNA damage repair mechanisms, potentially increasing susceptibility to tumors. However, several studies have investigated the association between ERCC2 polymorphisms and the risk of gynecological tumors, but the results have been inconsistent. Therefore, we performed this meta-analysis to estimate these associations more precisely.ObjectIn this paper, we summarized a larger sample for meta-analysis to explored the relationship between the polymorphisms of the ERCC2 Lys751Gln, Asp312Asn, and Arg156Arg and gynecological tumors.MethodsWe conducted a systematic search for relevant case-control studies in PubMed, the Cochrane Library, Embase, and the Web of Science databases, covering studies up to October 2024. The odds ratio (OR) and its 95% confidence interval (CI) were calculated using Stata 17 software.ResultsFinally, a total of 19 studies (9433 cases and 13144 controls) were included. 17 studies (3742 cases and 5591 controls) were conducted on the Lys751Gln polymorphism. Additionally, 9 studies(2,170 cases and 3,582 controls)were available for the Asp312Asn polymorphism, while 8 studies (3,521 cases and 3,971 controls)were included for the Arg156Arg polymorphism. Of these, 16 focused on ovarian cancer, 8 on cervical cancer, and 10 on endometrial cancer. The ERCC2 Lys751Gln polymorphism was found to increase the risk of gynecologic neoplasms(C vs A:OR 1.33, 95% CI 1.06-1.66;CC+CA vs AA:OR 1.33, 95% CI 1.11-1.59). Subgroup analysis by cancer type indicated an association of the Lys751Gln polymorphism with the development of ovarian cancer (CC+CA vs AA:OR 1.39, 95% CI 1.04-1.86), while no significant correlation was observed with cervical and endometrial cancers. Further subgroup analyses revealed that the Lys751Gln polymorphism increased the risk of gynecologic neoplasms in Caucasian and African populations, as well as in hospital-based studies. In contrast, the ERCC2 Asp312Asn polymorphism did not elevate the risk of gynecologic neoplasms, and the recessive gene variant was even protective against cervical cancer (AA vs GA+GG : OR 0.53, 95%CI 0.34-0.83, P=0.005). Additionally, this study did not find an association between the Arg156Arg polymorphism and susceptibility to gynecologic tumors.ConclusionThe ERCC2 Lys751Gln polymorphism is associated with an increased risk of gynecological tumors, particularly ovarian cancer. However, the Asp312Asn and Arg156Arg polymorphisms do not appear to elevate susceptibility to gynecological tumors. Even the recessive gene model of Asp312Asn polymorphism may have a protective effect on cervical cancer.